Approach to drug allergies in the childhood - Yazıcıoğlu, Mehtap (Turk Pediatri Ars, 2014)
Drug reactions (DR) are adverse or harmful effects of drugs. They constitute 6.5% of all hospital admissions. DR develops with a rate of 15% in patients who are treated by hospitalization. The possibility of DR should be considered in the differential diagnosis when any medical problem occurs in a person who uses medication. Detailed history and physical examination are directive in differentiation, if the reaction is a result of immune mechanisms. Although diagnostic tests are limited, they are beneficial according to the effective immune mechanism and presence of organ-specific or systemic findings. In children, the major difficulty in the diagnosis of DR is differentiation of maculopapular drug eruptions from viral exanthem which is observed very commonly in this age group. In treatment of allergic reactions, the first step is to immediately discontinue the responsible drug. Avoidance of using over-the-counter drugs and use of drugs orally if possible are important in terms of prevention of drug allergies. Cross-reactivity between drugs with similar structure should be considered when choosing an alternative drug. If an alternative drug or a drug which would not lead to cross-reaction can not be found, the drug is administered by desensitization. In this article, the apporach to drug allergies in children will be evaluated in accordance with current guidelines.